Polymerization in space. Permian period - Lyubimova, T.P.; Kostarev К.G.; Denisova М.О. (Perm Federal Research Centre Journal, 2025)
A brief review of experimental and theoretical studies carried out at the institutes of the Perm Scientific Centre of the Ural Branch of the Russian Academy of Sciences and devoted to the study of gravity-sensitive mechanisms of the polymerization process is presented. Based on the results of the research, the «Gel-1» space experiment (orbital station «Mir» 1992) was prepared and conducted. Using the data of the experiment, recommendations were developed for obtaining highly homogeneous polymer materials and polymers with a given distribution of physical and chemical properties, including in-ground conditions. Some of the works started back in the 1990s are successfully continued up to the present time. These are mainly studies of the peculiarities of composite materials curing in the conditions of open space as one of the most promising directions of creating large-size objects near the Earth and on the Moon surface.